Informed consent in clinical trials: Implementing methods to improve patient understanding in cancer research—A quality improvement initiative in a sarcoma trials unit. Issue 28 (1st October 2022) - Goggin, Caitriona; Al-Badri, Bader; Stansfeld, Anna; Barquin, Elizabeth; Durand, Benjamin; Nguyen, Thuy-Giang; Mahalingam, Preethika; Ayeni, Eniola; Napolitano, Andrea; Zaidi, Shane; Miah, Aisha; Jones, Robin Lewis; et al.
Abstract : 335 Background: Clinical trials are considered the cornerstone of improving outcomes for cancer patients. The understanding of an individual patient of the trial on which they are enrolled can vary significantly, with some studies demonstrating poor patient understanding of their involvement in trials. This exploratory study aimed to improve patient understanding of clinical trials and patient experience of the informed consent process by implementing measures to present complex trial information in alternative formats. Methods: The project was undertaken in a sarcoma trials unit in a specialist cancer treatment centre. Baseline knowledge was assessed using an adapted version of the Quality of Informed Consent (QuIC) questionnaire. A decision-aid was created following focus group discussions with stakeholders, focussing on key trial questions for patients, such as consent, the research description, risks, benefits, and alternatives to the trial. A patient education video was produced by the research team, explaining general aspects of clinical trials in patient-friendly language. The decision-aids and videos were distributed during the informed consent process of trial recruitment over a 12-week period. The patient group was assessed with post-intervention questionnaires. Statistical analysis was descriptive due to the small numbers. Results: Thirty sarcoma patients participated in the project, including baseline assessment of 15 patients previously enrolled on study, and 15 patients considering participation in a trial who underwent the intervention. 100% (n = 15) of the interventional group found the video and decision-aid useful. 60% (n = 18) of patients had a university level education, indicating a well-educated population. A pre- and post-intervention comparison demonstrated an improved understanding of 10 key elements of clinical trial information as shown in Table. Conclusions: Our exploratory study has shown that patient education tools including decision-aids and patient videos can be successfully implemented to help improve patient understanding of clinical trial information and may be of benefit in other trials units. Further larger studies are required to confirm these findings.Pre and post intervention comparison of patient-reported understanding of clinical trial information. Trial Topic Assessed Patient-reported full understanding (5/5 Likert scale) Pre-intervention N = 15 (%) Post-intervention N = 15 (%) What trial is trying to answer 9 (60) 15 (100) Point of contact 13 (87) 15 (100) Voluntariness of participation 14 (93) 15 (100) Experimental component 9 (60) 14 (93) Benefits of trial 12 (80) 13 (87) Risks of trial 10 (67) 13 (87) Treatment/procedures involved 12 (80) 13 (87) Confidentiality of medical records 9 (60) 12 (80) Alternatives of trial 6 (40) 9 (60) Duration of trial 6 (40) 9 (60)